Kuliah Kerja Nyata Penerapan Teknik Token Economy untuk Meningkatkan Minat Belajar Siswa Melalui Program Rumah Belajar Desa Pasa Kubang, Kecamatan Lembah Segar, Kota Sawahlunto - Anggra Ghifari; Dwi Rahayu; Hafidzh Sukri A; Ilhamdi Fatihah; Khoirunnisa Salsabila Trianti; Melsi Wulandari; Nuzul Rizki Rahmadani; Ratih Novita Sari; Ririn Aprilia; Ririn Julia; Siti Zahra Zafira; Viona Deswan Wulandari; Winda Aprilia Sari; Wulan Tri Iswandi; Zizi Khairunisa; Eval Edmizal (Lembaga Pengembangan Kinerja Dosen, 2024)
He application of token economy techniques in education has received significant attention because of its ability to increase students' interest in learning. This technique functions by providing rewards in the form of tokens to students as incentives for positive behavior and academic achievement. The benefits of using a token economy are not only limited to increasing motivation, but also creating a more fun and interesting learning atmosphere. In the context of home learning programs, this technique is implemented by providing a conducive learning environment, where students can earn tokens as recognition for their efforts. The results of this implementation show a positive impact on students' interest in learning, with more students being active and involved in learning activities. Evaluation of the effectiveness of the home learning program shows that the application of token economy techniques can be an effective solution for improving the quality of education in schools. Home learning is one solution to boredom in the current learning situation. Through this activity, children will gain new insights and knowledge and hone their creativity.